Preparation and characterization of Bi4–xPrxTi3O12 solid solutions - A. I. Klyndyuk; E. A. Chizhova; A. I. Poznyak (Chimica Techno Acta)
The Bi4–xPrxTi3O12 (BPT) solid solutions (x = 0.05, 0.10, 0.15) with small praseodymium content were prepared by solid-state method. Thermal, electric, and dielectric properties of BPT were studied. It was revealed that BPT titanates crystalize in аn orthorhombic structure and exhibit p-type semiconductivity. Dielectric constant of BPT increased, Curie temperature (TC), electrical conductivity and dielectric losses decreased, but lattice parameters and thermo-EMF coefficient remained practically unchanged with the increase of praseodymium content in layered Bi4–xPrxTi3O12. It was determined that activation energy of direct current (DC) electrical conductivity and linear thermal expansion coefficient (LTEC) of BPT changes at ferroelectric (FE) → paraelectric (PE) phase transition. The activation energy and LTEC changed below and above TC from 1.08–1.56 eV to 0.45–0.86 eV and from (9.10–10.80)×10–6 K–1 to (13.12-14.61)×10–6 K–1, respectively. The AC electrical conductivity studies of BPT illustrated short-range order with ionic translations assisted by small-polaron hopping.